Association of TrkA and APP Is Promoted by NGF and Reduced by Cell Death-Promoting Agents - Canu, Nadia; Pagano, Ilaria; La Rosa, Luca Rosario; Pellegrino, Marsha; Ciotti, Maria Teresa; Mercanti, Delio; Moretti, Fabiola; Sposato, Valentina; Triaca, Viviana; Petrella, Carla; Maruyama, Ichiro N.; Levi, Andrea; et al. (Frontiers in Molecular Neuroscience, 2017)
The amyloid precursor protein (APP) interacts with the tropomyosin receptor kinase A (TrkA) in normal rat, mouse and human brain tissue but not in Alzheimer’s disease (AD) brain tissue. However, it has not been reported whether the two proteins interact directly, and if so, which domains are involved. Clarifying these points will increase our understanding of the role and regulation of the TrkA/APP interaction in normal brain functioning as well as in AD. Here we addressed these questions using bimolecular fluorescence complementation (BiFC) and the proximity ligation assay (PLA). We demonstrated that exogenously expressed APP and TrkA associate through their juxtamembrane/transmembrane domains, to form a complex that localizes mainly to the plasma membrane, endoplasmic reticulum (ER) and Golgi. Formation of the complex was inhibited by p75NTR, ShcC and Mint-2. Importantly, we demonstrated that the association between endogenous APP and TrkA in primary septal neurons were modified by NGF, or by drugs that either inhibit ER-to-Golgi transport or perturb microtubules and microfilaments. Interestingly, several agents that induce cell death (amyloid β (Aβ)-peptide, staurosporine and rapamycin), albeit via different mechanisms, all caused dissociation of APP/TrkA complexes and increased production of C-terminal fragment (β-CTF) APP fragment. These findings open new perspectives for investigating the interplay between these proteins during neurodegeneration and AD.